The Role of the Principal in Strengthening Character Education in School By Involving Tripusat Pendidikan - Nasrika, Nasrika; Zulkarnain, Wildan; Sunarni, Sunarni (Universitas Negeri Malang, 2021)
Abstract: This study describes: (1) the role of the principal in the implementation of character education in schools; (2) the involvement of